2016
DOI: 10.1371/journal.pone.0158744
|View full text |Cite
|
Sign up to set email alerts
|

An Indirect Defence Trait Mediated through Egg-Induced Maize Volatiles from Neighbouring Plants

Abstract: Attack of plants by herbivorous arthropods may result in considerable changes to the plant’s chemical phenotype with respect to emission of herbivore-induced plant volatiles (HIPVs). These HIPVs have been shown to act as repellents to the attacking insects as well as attractants for the insects antagonistic to these herbivores. Plants can also respond to HIPV signals from other plants that warn them of impending attack. Recent investigations have shown that certain maize varieties are able to emit volatiles fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Egg deposition or treatment with elicitors did not show particular effects in commercial standard maize hybrids, indicating a possible loss of defense traits in plants subjected to artificial selection and breeding (Mutyambai et al, 2016;Tamiru et al, 2017) and, as in the case of HR-like necrosis in B. nigra (Griese et al, 2017), highlighting the role of plant genotype in defense mechanisms.…”
Section: Bertea Et Almentioning
confidence: 92%
See 1 more Smart Citation
“…Egg deposition or treatment with elicitors did not show particular effects in commercial standard maize hybrids, indicating a possible loss of defense traits in plants subjected to artificial selection and breeding (Mutyambai et al, 2016;Tamiru et al, 2017) and, as in the case of HR-like necrosis in B. nigra (Griese et al, 2017), highlighting the role of plant genotype in defense mechanisms.…”
Section: Bertea Et Almentioning
confidence: 92%
“…Lepidopteran egg elicitors can also induce the production of oviposition-induced plant volatiles (OIPVs) enabling the plants 7) to attract egg or larval parasitoids, that upon locating their hosts, inject their own eggs and kill the lepidopteran instars to feed their off-spring (Tamiru et al, 2011;Fatouros et al, 2012;Cusumano et al, 2015;Ponzio et al, 2016) or 8) insectivorous birds (Mrazova et al, 2019). In addition, OIPVs can also prime 9) neighboring plants (Mutyambai et al, 2016;Guo et al, 2019).…”
Section: Egg-induced Indirect Plant Responsesmentioning
confidence: 99%
“…Plant to plant communication is known to be a mechanism of pest control through herbivore-induced plant volatiles (HIPVs) (Khan et al 2001;Cook et al 2007;Heil 2008;Tamiru et al 2012;Magara et al 2015;Mutyambai et al 2016). Studies have shown that B. brizantha is preferred to maize for oviposition by gravid C. partellus (Midega et al 2011;Cheruiyot et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The current results suggest that oviposition‐induced volatiles can also prime plant defences; this finding complements other recent work showing that oviposition‐induced volatiles also play a communicative function in indirect plant defence by serving as foraging cues for natural enemies of herbivores, as well as herbivores themselves. For example, both egg and larval parasitoids showed a stronger preference for maize plants exposed to volatiles of plants infested by eggs of the herbivore Chillo partellus than control plants (Mutyambai et al 2016). Ovipositing herbivores were also seen to avoid poplar plants exposed to volatiles from egg‐infested neighbours (Guo et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Plants infested with P. brassicae eggs were also found to flower earlier and produce significantly more seeds than control plants (Lucas‐Barbosa et al 2013; Pashalidou et al 2015b) and to emit volatiles that recruit larval parasitoids (Pashalidou et al 2013; Pashalidou et al 2015b). Recent studies in other systems have also reported effects of volatiles induced by herbivore oviposition, including enhanced parasitoid attraction in teosinte (Mutyambai et al 2016) and decreased herbivore recruitment in poplar (Guo et al 2019). In the light of these findings, we hypothesised that it might be adaptive for B. nigra plants themselves to detect and respond to volatile cues associated with the presence of P. brassicae eggs.…”
Section: Introductionmentioning
confidence: 99%